Função sócio-ambiental da propriedade privada urbana - Mesquita, Margarida Maria Moura (2009)
Socio-environmental function of urban private property is the central theme of this work. The study includes a historical analysis of the property and its development, which no longer has an absolute character going to have a social character, impacting not only on matters of urban as well as on issues relating to protecting the environment and quality of life. The theme of the need to review what we call theoretical assumptions of socio-environmental function of urban private property, where situate the origin of social function for advancing the examination of its various manifestations in different spheres such as environment, based on the qualifications legal. This approach requires, in addition, an approach to constitutional principles as a basis of our legal system apart from the issue, controversy still the limits and restrictions for the property may ultimately suffer for a balanced and sustainable society, phenomena that are legal underlying these instruments. Established the theoretical basis, continuing with the verification of their practical application, which is the analysis of the contribution of doctrine for understanding the rules of the articles contained in our Federal Constitution, Civil Code and other laws sparse, and, yet, No examination of the contribution of jurisprudence. In all, the apparent attempt to demonstrate that the use of the property directly impacts the quality of life of mankind, therefore, the comprehensiveness of the importance that the socio-environmental function of urban private property has to our lives, as part of harmonization of interests social and individual directed to achieving social justice